Assessment of the association between cytomegalovirus DNAemia and subsequent acute graft‐versus‐host disease in allogeneic peripheral blood stem cell transplantation: A multicenter study from the Spanish hematopoietic transplantation and cell therapy group. Issue 4 (18th May 2021) - Bueno, Felipe; Solano, Carlos; Vázquez, Lourdes; Giménez, Estela; de la Cámara, Rafael; Albert, Eliseo; Rovira, Montserrat; Espigado, Ildefonso; Martín Calvo, Carmen; López‐Jiménez, Javier; Suárez‐Lledó, María; Chinea, Anabella; et al.
Abstract: The potential role of active CMV infection in promoting acute Graft‐versus‐Host Disease (aGvHD) in allogeneic hematopoietic stem cell transplantation (allo‐HSCT) remains a matter of debate. We further addressed this issue conducting a retrospective, observational, multicenter study of 632 patients subjected to allogeneic peripheral blood HSCT at 20 Spanish centers. Monitoring of CMV DNA load in plasma or whole blood was performed by real‐time PCR assays. Cumulative incidence of CMV DNAemia was 48.9% (95% CI, 45%‐52.9%), of any grade aGvHD, 45.6; 95% (CI, 41.3%‐50.1%), and of grade II‐IV aGvHD, 30.7 (95% CI, 24.9%‐36.4%). Overall, development of CMV DNAemia at any level resulted in an increased risk of subsequent all grade (HR, 1.38; 95% CI, 1.08 ‐ 1.76; P  = .009) or grade II‐IV (HR, 1.58; 95% CI, 1.22 ‐ 2.06; P  = .001) aGvHD. The increased risk of aGvHD linked to prior occurrence of CMV DNAemia was similar to the above when only clinically significant episodes were considered for the analyses (HR for all grade aGvHD, 1.48; 95% CI, 1.13 ‐ 1.91; P  = .041, and HR for grade II‐IV aGvHD, 1.53; 95% CI. 1.13‐1.81; P  = .04). The CMV DNA doubling time in blood was comparable overall in episodes of CMV DNAemia whether followed by aGvHD or not. Whether CMV replication is a surrogate risk marker of aGvHD or it is causally involved is an important question to be addressed in future experimental research.